Feasibility Study For The Development of TPS3R Waste Bank - Widayat, Prama; Sri Maryanti; Nurhayani Lubis; Safrul Rajab (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2022)
The existence of a waste processing site is very urgent because what is currently happening is a landfill that accumulates waste. Then there was the waste bank as one of the waste processing sites in Pematang Pudu Village, Mandau District, Bengkalis Regency. But it has not been able to optimally manage waste, where the population of Mandau District is 150,806 people while Pematang Pudu Village is 29,986 people and the potential for waste is 15 tons per day. So far, only 0.5 tons of waste banks can manage per day. So it is necessary to make a breakthrough by building TPS3R which has a larger capacity, at least 2 tons per day. This capacity can continue to be developed and be able to create job opportunities for the community.